IMPLEMENTASI PEMBELAJARAN RADIKAL UNTUK MENINGKATKAN PENGUASAAN AKSARA MANDARIN MAHASISWA PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Valentriana, Prisila; Veronica, Tjen; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Radical literacy teaching method is a teaching method that uses radicals for literacy. The author uses the radical literacy teaching method to improve the ability of the 2021 Class A students majoring in Chinese language education at Tanjungpura University to master Chinese characters. The author uses observation method, test method, and questionnaire survey. Through the test method, the author found that the scores of the 2021 Class A students majoring in Chinese language education at Tanjungpura University have increased by an average of 22.4%. 33% of students passed the pre-test. After passing the radical literacy teaching method, 85% of the students passed the post-test. Therefore, using the radical literacy teaching method can help students memorize Chinese characters, understand the meaning of words and recognize the pinyin of words. The results of the final analysis show that the 2021 Class A students majoring in Chinese education can improve their ability to master Chinese characters by applying the radical teaching method